Incidence of Rota Virus Gastroenteritis among Vaccinated and Non-vaccinated Children Less Than Two Years Old in Ramadi City, Iraq - Muneam A. Ayyed; Mohsen F. Al-Dulaim; Rafi K. Al-Ani; Saleem O. G. Al-Mawla (Al-Anbar Medical Journal)
Background: Acute gastroenteritis is a major cause of health problem among children in undeveloped countries, where the rotavirus is the most widely recognized etiology. Objectives: This study aimed to find out the incidence of rotavirus in diarrheal children less than two years of age in both vaccinated and non-vaccinated children with rotavirus vaccine. Also to determine some risk factors associated with this disease. Materials and methods: A cross-sectional study was conducted for 6 months, from the first of June 2018 to the first of December 2018.  Six hundred child less than two years old with acute gastroenteritis was included in the study. Stool tests were sent to the lab for identification of rotavirus antigen using the ELISA technique in the stool. Stool samples belong to 300 cases of vaccinated children with the rota vaccine and the other 300 cases belong to non-vaccinated children. A questionnaire data form regarding age, gender, maternal education, residence and type of feeding was taken from each infected child. Results: Out of a total of 600 stool samples of children with acute gastroenteritis, rotavirus was detected in 192 (32%) samples. Among 300 non-vaccinated patients, 123 (41%) were rotavirus positive, and among other 300 vaccinated patients 69 (23%) were rotavirus positive. The majority of cases were reported in the age group 6-12 months. Bottle-feeding and mothers of the low educational level were found to increase the incidence of rotavirus infection. Conclusion: Incidence of rotavirus gastroenteritis was predominant in diarrheal children. Vaccination with the rotavirus vaccine decreases the rotavirus gastroenteritis in diarrheal children.